2014
DOI: 10.1111/mec.12630
|View full text |Cite
|
Sign up to set email alerts
|

Replicate divergence between and within sounds in a marine fish: the copper rockfish (Sebastes caurinus)

Abstract: Understanding the factors that influence larval dispersal and connectivity among marine populations is critical to the conservation and sustainable management of marine resources. We assessed genetic subdivision among ten populations of copper rockfish (Sebastes caurinus) representing paired samples of outer coast and the heads of inlets in five replicate sounds on the west coast of Vancouver Island, British Columbia, using 17 microsatellite DNA loci. Overall, subdivision (F ST ) was low (F ST = 0.031, P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
(87 reference statements)
0
9
1
Order By: Relevance
“…The present study found discordance between the mtDNA and msDNA loci results; the former suggested that Korean S. thompsoni comprised a single panmictic group, but the latter suggested that it comprised two genetically distinct clusters: Cluster 2 was predomi- null alleles produced very similar results of genetic differentiation as when they were included (Dick, Shurin, & Taylor, 2014;Lane, Symonds, & Ritchie, 2016;Underwood, Travers, & Gilmour, 2012).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The present study found discordance between the mtDNA and msDNA loci results; the former suggested that Korean S. thompsoni comprised a single panmictic group, but the latter suggested that it comprised two genetically distinct clusters: Cluster 2 was predomi- null alleles produced very similar results of genetic differentiation as when they were included (Dick, Shurin, & Taylor, 2014;Lane, Symonds, & Ritchie, 2016;Underwood, Travers, & Gilmour, 2012).…”
Section: Discussioncontrasting
confidence: 77%
“…The presence of null alleles, which caused an excess of homozygotes, can overestimate the levels of genetic differentiation (Chapuis & Estoup, ). However, many studies demonstrated that the analysis conducted excluding the loci with null alleles produced very similar results of genetic differentiation as when they were included (Dick, Shurin, & Taylor, ; Lane, Symonds, & Ritchie, ; Underwood, Travers, & Gilmour, ). Furthermore, it is known that null alleles could not change the overall patterns of genetic population revealed in ms loci analysis (Carlsson, ).…”
Section: Discussionmentioning
confidence: 97%
“…This may be caused by heterozygote deficits, and there was heterozygote deficiency in 30 of the studied loci. Although null allele is also an important contributor for the heterozygote deviation in marine fish (Dick et al, 2014), it is unlikely that null allele is the main cause of the deviations observed in this study, because only a few loci had a high frequency of null alleles (e.g., RFs315, Kss18). The overall genetic diversity in S. schlegelii in this study was comparable to that previously reported using mtDNA and microsatellite markers (Zhang et al, 2016;Gao et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…The overall mean G ST across loci is 0.027, very close to the F ST value 0.031 obtained by Dick et al . (). Single‐locus G ST and H S estimates are not correlated, with a correlation coefficient of 0.011 and a P value of 0.649.…”
Section: Resultsmentioning
confidence: 97%